Career Development, Transformational Leadership, and Compensation on Turnover Intention with Employee Engagement as Intervening Variable - Diananda, Erika; Herminingsih, Anik (International Journal of Indonesian Business Review, 2025)
Purpose – This study aims to analyze the effect of career development, transformational leadership, and compensation benefits on turnover intention with employee engagement as an intervening variable in PT. DSRL. Methodology/approach – The research design used is quantitative descriptive research using the total population of 70 respondents. Data analysis using the Smart PLS 4.0 application which consists of testing the inner model and outer model. Findings – It The results found that career development, transformational leadership, and compensation have a positive and significant effect on employee engagement. The results found that career development, transformational leadership, compensation, and employee engagement have a negative and significant effect on turnover intention. The results found that career development, transformational leadership, and compensation have a negative effect on turnover intention through employee engagement as an intervening variable.